Some issues of adaptation of the post-soviet managerial elite to new social relations (socio-cultural aspect) - D. V. Maslov (Управление)
The problem of adaptation of the post-Soviet administrative elite to the social relations formed as a result of reforms in the USSR - Russia at the end of XX century - in the beginning of XXI century. The peculiarity of the study is the consideration of the problem in the General context of social changes of this period. The author shows that the usual theoretical and methodological schemes based on the opposition of the late Soviet and modern Russian political elite do not contribute to the approach to the truth. Thus, reliance only on official documents, statistics and other sources reflecting the external side of the processes under study appears to be insufficient. Therefore, the attention is drawn to the need for more active involvement of sources of personal origin, allowing to trace the evolution of consciousness of the ruling elite, the change of its stereotypes, values and norms. The such issues of adaptation of the modern Russian elite to new conditions as changing its attitude to ideology, to the goals of education, to the procedures of admission to the civil service, its passage and withdrawal from it, are highlighted. It is noted that in General, the post-Soviet administrative elite successfully and very quickly adapted to radical social changes. The number of factors that have ensured this adaptability is analyzed. It is noted that a special role in the processes of adaptation of the elite was played by factors of socio-cultural order: the ability to play by changing rules, moral and ideological relativism, following the established traditions, formed norms and values. However, it is necessary to take into account that the adaptation process is not completed, neither in elite nor in society in General. Thus, the process of adaptation of the Russian political elite is considered against the General background of post-Soviet transformation, which allows a deeper understanding of the mechanisms and results of the development of Russian society as a whole.